Uses of ChatGPT for the revision of academic texts: some considerations - Salas Acuña, Erick Francisco; Amador Solano, María Gabriela (Innovaciones Educativas, 2023)
The purpose of this contribution is to provide some recommendations on the use of ChatGPT for proofreading academic texts. Proofreading is a fundamental phase of the writing process that involves improving both the rhetorical and content aspects of texts. However, since it is a particularly difficult task that requires, in addition to linguistic knowledge, a significant amount of reflection, it is common for students to omit it or limit themselves to evaluating only orthographic aspects, leaving aside other levels of greater complexity. Because of this, it is necessary to develop initiatives that guide and facilitate this task. In this regard, the proposed analysis rehearses some of the possibilities offered by artificial intelligence to support students entering university with the revision and rewriting of their texts. For this purpose, fragments of texts written by students were used and adapted in order to test the effectiveness of the platform for diagnosing and correcting cohesion-related problems. The main conclusion is that tools such as ChatGPT can contribute to the improvement of writing processes, while favoring autonomous learning in the revision of texts from an innovative perspective; however, they do not replace the responsibility of the writer to revise his or her text, but only complement it.